Variceal bleeding due to idiopathic portal vein thrombosis in a 15‐year‐old boy. Issue 8 (20th July 2019) - Dilber, Dario; Habek, Dubravko; Hrgović, Zlatko; Čerkez Habek, Jasna; Gradišer, Marina
Abstract: Portal vein thrombosis is an important cause of portal hypertension in the pediatric population. It is a rare and potentially fatal condition with diverse underlying pathology. A successfully managed case, without an identified etiology, is reported herein. Abstract : Portal vein thrombosis is an important cause of portal hypertension in the pediatric population. It is a rare and potentially fatal condition with diverse underlying pathology. A successfully managed case, without an identified etiology, is reported herein.